Combined modal split and assignment model for the multimodal transportation network of the economic circle in China - Li, Shuang; Deng, Wei; Lv, Yisheng (Transport, 2009)
Economic circles have been formed and developing in China. An economic circle consists of more than one closely adjoining central cities and their influence zones. It is always the major engine for the development of one country's economy and even for the world economy. A combined modal split and assignment model with deterministic travel demand is proposed for modelling passengers’ choices of intercity bus and train which are two main competing modes in the multimodal transportation network of the economic circle. The generalized travel cost model of highway and railway are used incorporating travel time, ticket fare and passenger's discomfort. On the highway network, the interactions of private vehicles and intercity buses are asymmetric. Thus, a variational inequality formulation is proposed to describe the combined model. The streamlined diagonalization algorithm is presented to solve the combined model. The multimodal transportation network based on Yangtze River Delta economic circle is presented to illustrate the proposed method. The results show the efficiency of the proposed model.First published online: 27 Oct 2010